SELF-REGULATED LEARNING: IMPLICATION FOR SCHOOL COUNSELOR - Anandha Putri Rahimsyah; Nurul Hikmah (Study Program Guidance and Counseling, Univesitas Pendidik, 2022)
21st-century learning requires students to have many skills that support their academic achievement in school. One of the predictors of student learning achievement in school is self-regulated learning. Self-regulated learning assists students not only in establishing an efficient learning approach, but also in identifying a lack of knowledge and determining the help required to aid their learning process. Low student motivation, the adoption of inefficient tactics, and low self-regulation can all have an impact on student academic achievement. The purpose of this study is to define the role of school counselors in removing impediments to students' success, improving students' learning environments, and supporting students' academic progress as implications for school counselors. The method used in this study is a systematic literature review. Data were obtained from various research or non-research scientific articles and books relevant to the research title. The study results stated that school counselor services support students' academic achievement, namely self-regulated learning. The focus of services for self-regulated learning students is related to increasing metacognitive, motivational, and behavioral. This study explained several approaches to help students have self-regulated learning that supports academic achievement.